2019
DOI: 10.3390/ijerph17010004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Quality of Life in Patients Treated for Maxillofacial Fractures

Abstract: Maxillofacial fractures (MFF) belong to the major modern medicine and public health concerns. The recovery from MFF is associated with a number of social problems. The patient’s mood may be affected by the change in self-image and lack of satisfaction with life, in many cases leading to a deepening of mental health disorders, resulting in alcoholism, loss of job or conflicts in the area of family life. The aim of this study was to evaluate the quality of life of patients with MFF, with respect to demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
14
0
3
Order By: Relevance
“…The findings of this study and previously published papers [5,8,16] indicate that psychological and social problems are frequent among patients recovering from facial trauma. It is important to emphasize multiprofessional collaboration in providing services that support patient recovery.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings of this study and previously published papers [5,8,16] indicate that psychological and social problems are frequent among patients recovering from facial trauma. It is important to emphasize multiprofessional collaboration in providing services that support patient recovery.…”
Section: Discussionsupporting
confidence: 75%
“…Sikora et al [16] observed similarly a negative impact of maxillofacial trauma on the quality of life, followed by the tendency to recover with treatment. The factors affecting HRQoL have been analyzed, with the aid of the SF-36 questionnaire, immediately and 3 months after the treatment of maxillofacial fractures in 227 patients.…”
Section: Discussionmentioning
confidence: 93%
“…Lesions of the dental and maxillary apparatus, which develop in cases of traffic accidents, domestic, industrial or other injuries, lead to a sharp decrease in dental health, and accordingly -to a decrease in quality of life associated with post-traumatic changes in dental status [1,6,7,12,13,15,16]. At the stage of forensic dental assessment of the severity of the lesion, it is advisable to conduct a comparative analysis of the integrated criterion of quality of life in terms of differences in its indicators before and after injury, which allows to predict the potential for recovery of levels of relevant physical, functional and social domains.…”
Section: Official Journal Of the International Academy Of Integrativementioning
confidence: 99%
“…At the stage of forensic dental assessment of the severity of the lesion, it is advisable to conduct a comparative analysis of the integrated criterion of quality of life in terms of differences in its indicators before and after injury, which allows to predict the potential for recovery of levels of relevant physical, functional and social domains. complex dental treatment [7,12,15].…”
Section: Official Journal Of the International Academy Of Integrativementioning
confidence: 99%
“…A fracture in this area can affect facial appearance, function, and quality of life. [ 1 ] To restore aesthetics, function, and quality of life, it is essential to completely diagnose these fractures for effective management.…”
Section: Introductionmentioning
confidence: 99%